Can the management of blood sugar levels in gestational diabetes mellitus cases be an indicator of maternal and fetal outcomes? The results of a prospective cohort study from India - Rajesh Jain; Sanjeev Davey; Anuradha Davey; Santosh K Raghav; Jai V Singh (Wolters Kluwer Medknow Publications, 2016)
Background: Gestational diabetes mellitus (GDM) is emerging as an important public health problem in India owing to its increasing prevalence since the last decade. The issue addressed in the study was whether the management of blood sugar levels in GDM cases can predict maternal and fetal outcomes. Materials and Methods: A prospective cohort study was done for 1 year from October 1, 2013, to September 31, 2014, at 652 diabetic screening units as a part of the Gestational Diabetes Prevention and Control Project approved by the Indian Government in the district of Kanpur, state of Uttar Pradesh. A total of 57,108 pregnant women were screened during their 24-28th weeks of pregnancy by impaired oral glucose test. All types of maternal and perinatal outcomes were followed up in both GDM and non-GDM categories in the 2nd year (2013-2014) after blood sugar levels were controlled. Results: It was seen that for all kinds of maternal and fetal outcomes, the differences between GDM cases and non-GDM cases were highly significant (P < 0.0001, relative risk >1 in every case). Moreover, perinatal mortality also increased significantly from 5.7% to 8.9% when blood sugar levels increased from 199 mg/dl and above. Perinatal and maternal outcomes in GDM cases were also significantly related to the control of blood sugar levels (P < 0.0001). Conclusion: Blood sugar levels can be an indicator of maternal and perinatal morbidity and mortality in GDM cases, provided unified diagnostic criteria are used by Indian laboratories. However, to get an accurate picture on this issue, all factors need further study.